Anti-Proliferative Activity of Rutin in Cancer - Chebrole, Shekinah (International Journal of Recent Advances in Multidisciplinary Topics, 2022)
Rutin, a powerful antioxidant, is said to have anti-cancer properties. Our study aims to prepare rutin-loaded chitosan nanoparticles (RCNPs) by an ion gelation method. These particles are characterized by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction spectroscopy (XRD), scanning electron microscopy (SEM). The FTIR spectrum of RCNP also showed the existence of various chitosan effective groups and peaks corresponding to rutin effective groups, indicating the successful encapsulation of rutin into chitosan ultrafine particles. By applying the Debye-Scherrer equation to his XRD data, his RCNP size was found to be 33.12 nm. SEM images revealed the surface porosity and rough analysis of RCNPs. The electromagnetic ability was found to be +0.68 mV, indicating the stability of the ultrafine particles. The entrapment efficiency (EE%) was found to be 68.7%, the loading efficiency (LE%) was 49.09%, and the recovery of RCNP was 41.08%. Based on the above test values, RCNP was found to be useful in various cancer cell lines, namely HeLa, MDAMB231, Panc-1, PC, was further tested in the MTT assay against exposed to antiproliferative activity, SK0V3. These results showed that rutin and RCNP had anti-proliferative effects only on the cell lines of SK0V3, and the effect of RCNP was greater than that of pure rutin. Based on this, we can hypothesize that rutin-loaded chitosan nanoparticles (RCNP’s) have a promising, prominent role in revolutionizing the treatment of cancer diseases.
Keywords: Rutin; Nanoparticles/Ultrafine particles; Loaded Chitosan; Anti-cancer activity; Ovarian cancer; Pancreatic cancer